Delivery of customizable compressive patterns to human limbs to investigate vascular reactivity. (25th October 2018) - Messere, Alessandro; Pertusio, Raffaele; Macrì, Chiara; Maffiodo, Daniela; Franco, Walter; De Benedictis, Carlo; Ferraresi, Carlo; Roatta, Silvestro
Abstract: Objective : Commercial devices for pneumatic compressive treatment of the limbs generally provide predefined stereotyped compressive profiles. The possibility to deliver compressive stimuli with a customizable pressure profile would be useful to differently probe the vascular reactivity to muscle compression (MC) and improve the understanding of MC-induced hyperemia. Aim of this study was the realization of a novel pneumatic system capable of generating adjustable and stable compressive conditions, preceding and following a 'standard' MC stimulus. Approach : A custom-made pneumatic system specifically built to this purpose is tested and characterized in 10 subjects. Three different compressive patterns were delivered to the leg: (1) a constant level: 50 mmHg for 50 s; (2) MC: 200 mmHg for 1 s; (3) a complex profile: 20 mmHg for 50 s, 200 mmHg for 1 s, 50 mmHg for 50 s. Main results : The implemented system allowed to deliver graded compressions to the limb characterized by fast transitions (0 to 200 mmHg in 0.5 ± 0.07 s) and stable plateau levels (50.4 ± 0.5 mmHg). Significance : A new, low-cost, pneumatic prototype has been presented and tested in the present study allowing to deliver compressive stimuli with pre-and post-compressions of adjustable level. This device has been conceived for research purposes and may find application in therapeutic compressive treatments.